Bioactivity -guided isolation of antimicrobial agent from Coleus amboinicus Lour (Torbangun) - Khattak, Muhammad Muzaffar Ali Khan; Taher, Muhammad (Submitted IIUM RMC, 2011)
The leaves of Coleus amboinicus from Indonesia (CAL-I) and from Malaysia, Coleus aromaticus (CAT-M), Pogostemon cablin (PC-M), Coleus blumei–red leaves (CBR-M), Coleus amboinicus– (CAL-M) Coleus blumei –purple leaves (CBP-M) were collected from different localities, freeze dried and extracted with aqueous methanol. The biological activity in vitro, especially in relation to total phenolic & flavonoid contents, antioxidant and antimicrobial activities were studied. Total phenolic content was determined according to the Folin-Ciocalteu method whilst antioxidant activity was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The antimicrobial activity of the extract was determined by making use of macro dilution and disc diffusion methods on two gram positive bacteria, two gram negative bacteria and on fungus as well. Furthermore, the toxicity was also assessed for the extracts by performing acute toxicity test. The phenolic content among the six Lamiaceae leaves extract showed significant difference (p<0.05) in result ranging from 55.21 - 95.17 mg GAE/g of dried samples. Pogostemon cablin (PC-M) had the highest content of phenolic followed by C. blumei (CBP-M). There were significant differences (p<0.05) of IC50 value of six Lamiaceae leaves extract ranging from 10.5 – 34.1 µg/ml. Among the species studied, Coleus amboinicus (CAL-M) and Pogostemon cablin (PC-M) showed higher antioxidant activity compared to the other leaves extracts. All leaves extracts showed activity at least against one strain of bacteria and result showed significant difference (p<0.05) between activities on the microorganism studied. On the contrary, all of the leaves extracts were not effective against C. albicans. The minimum inhibitory concentration (MIC) of all leaves extracts ranged from 1.0–2.0 mg/ml in inhibiting the growth of S. aureus, E. Coli, P. aeruginosa and B.subtilis. The acute toxicity test using C. Blumei leaves extract showed that there was no mortality of animals recorded at the highest dose of 5000 mg/kg body weight. This study shows that the extracts can be used as antioxidant and antimicrobial agent without having the toxic effect.